2020
DOI: 10.3892/ol.2020.11435
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of m6A RNA methylation regulators for the prognosis of hepatocellular carcinoma

Abstract: N6-methyladenosine (m 6 A) RNA methylation, which is related to cancer initiation and progression, is dynamically regulated by the m 6 A RNA methylation regulators (including 'writers', 'erasers' and 'readers'). However, the prognostic value of m 6 A RNA methylation regulators involved in hepatocellular carcinoma (HCC) carcinogenesis and progression remains to be elucidated. The aim of the present study was to determine the prognostic score in predicting the prognosis of HCC patients based on these regulators.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Molecular-level pan-cancer analyses have provided insights into the common features and heterogeneity of various human malignancies ( 2 ). For example, Cancer Cell Line Encyclopedia (CCLE) and The Cancer Genome Atlas (TCGA) were developed based on epigenomic, genomic, proteomic, and transcriptomic data from multiple human cancer cell lines and tissues ( 3 5 ). Pan-cancer analyses have also revealed the significance of specific genes and signaling pathways in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular-level pan-cancer analyses have provided insights into the common features and heterogeneity of various human malignancies ( 2 ). For example, Cancer Cell Line Encyclopedia (CCLE) and The Cancer Genome Atlas (TCGA) were developed based on epigenomic, genomic, proteomic, and transcriptomic data from multiple human cancer cell lines and tissues ( 3 5 ). Pan-cancer analyses have also revealed the significance of specific genes and signaling pathways in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…5,13,28 Recent papers also examined the role of m6A-regulated regulators in HCC prognosis. [16][17][18][19] However, the present study systematically analysed the prognostic value and expression profile of m6A regulators in HCC from the TCGA database and validated the results in the GEO database and clinical surgical samples.…”
Section: Discussionmentioning
confidence: 76%
“…15 Recent studies examined the role of m6A regulatory genes in HCC prognosis. [16][17][18][19] The present study systematically analysed the clinical and RNA-seq pertaining to HCC from The Cancer Genome Atlas (TCGA) database and evaluated the alterations of 13 m6A regulatory genes in HCC and their association with clinicopathological features. All of the results were validated in the Gene Expression Omnibus (GEO) database and clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has strongly suggested that CDK2/4/6, in particular the CDK2, are involved in RNA modifications. As m6A RNA methylation participates in the pathogenesis of multiple diseases including cancer, the potential roles of CDK2/4/6 in m6A RNA modification in human HCC require further investigations (Li et al 2020 ). Furthermore, CDK2 has been reported to phosphorylate the p27 KIP1 and RB proteins in cell cycle progression, the replication factors A and C in DNA replication, the NPAT in histone synthesis, and the nucleophosmin (NPM) in centrosome duplication (Meraldi et al 1999 ).Taken together these studies strongly suggested an important role of CDK2 in human HCC, and a CDK2/4/6 triple inhibitor, vanoxerine dihydrochloride, may have additional advantages and broader anti-cancer activities than CDK4/6 dual inhibitors for the treatment of human HCC.…”
Section: Discussionmentioning
confidence: 99%